Developing agent-based models of complex health behaviour. (November 2018) - Badham, Jennifer; Chattoe-Brown, Edmund; Gilbert, Nigel; Chalabi, Zaid; Kee, Frank; Hunter, Ruth F.
Abstract: Managing non-communicable diseases requires policy makers to adopt a whole systems perspective that adequately represents the complex causal architecture of human behaviour. Agent-based modelling is a computational method to understand the behaviour of complex systems by simulating the actions of entities within the system, including the way these individuals influence and are influenced by their physical and social environment. The potential benefits of this method have led to several calls for greater use in public health research. We discuss three challenges facing potential modellers: model specification, obtaining required data, and developing good practices. We also present steps to assist researchers to meet these challenges and implement their agent-based model. Abstract : Highlights: ABM is effective for modelling health behaviour embedded within the environment. Key challenges are: formulating rules, obtaining process data, and acquiring skills. Experience from other disciplines may be adapted for public health research. The potential benefits of ABM warrant the effort required.